Onezhskīĭ zalivʺ / Sostavleno vʺ 1915 g. po robotamʺ otdi︠e︡lʹnoĭ sʺemki Bi︠e︡lago mori︠a︡ 1886-1913 g. g. - Soviet Union. Gidrograficheskoe upravlenie (Leningrad : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenie SSSR; [Ленинград] : Морское министерство, Главное гидрографическое управление СССР, 1925)
Mal. korr. X-1920 g Bol. korr. X-1925 g; Мал. корр. X-1920 г Бол. корр. X-1925 г.; Relief shown by hachures. Depths shown by soundings and isolines.; Title translation: Onega Bay.; Margin title translation: White Sea, Onega Bay.; Includes note.; Selected lights shown in yellow and orange annotations.; "Sostavleno vʺ 1915 g. po robotamʺ otdi︠e︡lʹnoĭ sʺemki Bi︠e︡lago mori︠a︡ 1886-1913 g. g." = Compiled in 1915 according to the work of the surveys of the White Sea of 1886-1913.; Greenwich meridian.; "Masshtabʺ 1/252000 ili 3000 sazh. 7-ti fut. mi︠e︡ry v di︠u︡ĭmi︠e︡ po paralleli 64°30'" = Scale 1/252000 or 3000 7-foot fathoms in 1 inch on the 64°30' parallel.; "No. 588" -- margins Grayscale; 1:252,000